2011
DOI: 10.1111/j.1443-1661.2011.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Dilation for Achalasia Cardia: Reduction in Lower Esophageal Sphincter Pressure in Assessing Response and Factors Associated With Recurrence During Long‐term Follow Up

Abstract: Post-PD LES pressure measurement is useful to assess treatment response. Patients responding to the first session and those with post-PD LES pressure <10 mmHg tended to recur less. Age and gender did not influence outcome, which might be related to preferential use of a 35-mm balloon, particularly for male patients, during the first session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Therapy instead is directed towards disrupting or weakening the LES. Diminution of LES pressure after therapy is paramount in attaining relief from dysphagia [5,6] . Until recently, the three traditional options for this were botulinum (Botox) injection (BTI) into the LES, pneumatic dilation (PD) of the LES and surgical myotomy (often with subsequent fundoplication to minimize reflux).…”
Section: Prior Conventional Treatments For Achalasiamentioning
confidence: 99%
“…Therapy instead is directed towards disrupting or weakening the LES. Diminution of LES pressure after therapy is paramount in attaining relief from dysphagia [5,6] . Until recently, the three traditional options for this were botulinum (Botox) injection (BTI) into the LES, pneumatic dilation (PD) of the LES and surgical myotomy (often with subsequent fundoplication to minimize reflux).…”
Section: Prior Conventional Treatments For Achalasiamentioning
confidence: 99%
“…The median LES pressure significantly decreased from 39.9 mmHg (28.7-50.3 mmHg) to 28.1 mmHg (17.6-34.9 mmHg) after PD. Ghoshal et al 35 have reported 22.5 mmHg as a best cut-off value of post-treatment LES pressure differentiating responders and non-responders after PD. However, among the current study patients, only 28 patients (43.9%) showed post-treatment LES pressure within 22.5 mmHg even though they all showed symptom improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might stem from the different definitions used in the each study. In the study by Ghoshal et al, 35 response to PD was defined as a decrease in dysphagia score to 0 or 1 and/or total symptom score to ≤ 3 on follow-up visit after PD. However, we evaluated the symptom response by subjective satisfaction for symptom relief.…”
Section: Discussionmentioning
confidence: 99%
“…Recent use of HRM has suggested that those with classic achalasia (predominant apersistalsis of distal esophagus -Chicago classification type I) and those with esophageal smooth muscle compression pattern on manometry (Chicago classification type II) respond much better to PD than those with so-called 'vigorous' achalasia or achalasia with high-pressure waves in the distal esophagus on HRM (Chicago classification type III) [Pretap et al 2011]. The absolute value of baseline LES pressure is not a predictive factor, but failure to lower the LES pressure significantly (usually to <10 mmHg) is associated with a poor outcome with PD [Hulselmans et al 2010;Ghoshal et al 2012].…”
Section: Pneumatic Dilationmentioning
confidence: 99%